К вопросу установления обобщенных характеристик при расчете потерь на корону - Кохреидзе, Гиви Климентьевич; Мчедлишвили, Д. Т.; Пхакадзе, Ш. А. (НТУ "ХПИ", 2010)
In the work there is carried out generalization of the data of corona loss taking into account five groups of weather by constancy and change of the inception voltage stress. As a result of applying Lagrange's Interpolation Formula for average generalized experimental data we receive analytic expressions of relations in the two coordinate systems for the groups of weather. These results enable to calculate average annual corona loss in wires for which there are no direct measurements at the action lines.
On the issue of assignment of summarized characteristics in the process of calculation of corona loss
Keywords: линия электропередач; напряжение; погода